Facets of social geography International and Indian perspectives - Costa, Frank J. (Ed); Wadhwa, Vandana (Ed); Thakur, Baleshwar (Ed); Dutt, Ashok K. (Ed) (Delhi Foundation Books, 2012)
Introductory framework